THE TIME IS ALREADY HERE: Tax Administrations in Digital Evolution - Ksenija Cipek (NUST Business Review, 2019)
Tax administrations around the world face a new era of digital evolution. Tax policy is one of the most important policies of each country, so the time of new digital challenges cannot be ignored. Tax administrations have a huge amount of information that needs to be safe, confidential and disposed of in accordance with regulations and prescribed procedures. In addition to collecting tax revenues, one of the tasks of the tax administration is to serve taxpayers. In digital era, they try to ease the administrative burden on taxpayers using new technologies. New technologies are also used for the purpose of preventing tax frauds and determining the risk of taxpayers. What kinds of new technologies will be used by tax administrations depends on their estimate, but cannot be overlooked if they want to be efficient in their work. Tax legislation is also faced with new challenges such as the occurrence of crypto currency. The subject of this article is the emphasis on the possibilities of applying new technologies in tax administrations, the relationship between tax legislation and technology, the possibilities of digitization and the consideration of crypto currency issues.